The Effect of Gender on Problematic Internet Usage: A Meta-Analysis - Akbaş, Ufuk; Atalan Ergin, Derya; Tatlı, Cemre (Addicta: The Turkish Journal on Addictions, 2019)
The aim of this research is to analyze the effect of gender on problematic Internet usage by meta-analysis. Problematic Internet usage is defined by the deterioration of the important dimensions of individuals’ lives, such as family and work, the failure to control the usage and compulsive usage of individuals due to the usage of the Internet. It is known that adolescents use the Internet more than other age groups. Therefore, adolescents are thought to be able to use the Internet in a non-functional way, besides, differences in the usage and duration of Internet usage according to gender have also been reported. PIUS and PIUS-A is being used in investigations on problematic Internet usage in Turkey frequently. Thus, the findings of the studies using these measurement tools were used in the analysis of this research. As a result of the literature review, 30 studies including PIUS and PIUS-A were detected and four studies were excluded from the analysis according to different reasons, thus the analyses were performed on the findings of 26 studies. Average effect size is .385 according to fixed effect model and could be considered small and in favor of males. Similarly, in studies where the type of research and the measurement tool used are considered as moderator variables, the effect size is small and in favor of males. As a result, problematic Internet usage of male adolescents may be noted as higher. The results were discussed in the light of cultural differences and parental attitudes.To
Keywords: Problematic Internet usage; Gender; Meta-analysis; Adolescents; Technology